La Asertividad y el Clima Laboral en la empresa HIDROSIERRA S.A. en el cantón Baños. Tungurahua. - Franco Ilbay, Tatiana Lizbeth (2023)
The present research work aims to determine assertiveness and the Work Environment at HIDROSIERRA S.A in the Baños Tungurahua Canton. To this end, various data collection techniques were employed, including surveys of the company's employees and interviews with supervisors, in order to establish the relationship between our two study variables. Within organizations, assertiveness represents a modern system of management and leadership, which can assist in achieving a company's objectives more effectively. This is because it contributes to obtaining a suitable work environment, considering that individuals within a company, whether they are managers or operators, often directly or indirectly convey their emotions, attitudes, and feelings. As a result, it was primarily evident that assertiveness among employees is directly related to the work environment, as employees feel committed to the company. Assertiveness is a factor that directly influences the company's organizational climate. Handling it assertively and appropriately can make individuals feel more comfortable and pleasant, thereby fostering trust and credibility. This, in turn, directly impacts work productivity. Therefore, as a solution to the findings, improvement strategies are proposed. These strategies encompass objectives, goals, activities, beneficiaries, and responsible parties, all aimed at enhancing the work environment in the company.